In patients with asthma, does increasing the dose of inhaled corticosteroid at the onset of an asthma exacerbation improve outcomes over continuing the maintenance dose?. Issue 3 (March 2016) - Bostrom, Erik; Satre, Thomas
Abstract : Evidence‐Based Answer : No, increasing the dose of inhaled corticosteroid (ICS) for asthma exacerbations does not reduce the need for rescue systemic corticosteroids compared with maintaining the usual dose (SOR: A, meta‐analysis of RCTs).